2022
DOI: 10.3390/biom12091309
|View full text |Cite
|
Sign up to set email alerts
|

6-Furopyridine Hexamethylene Amiloride Is a Non-Selective P2X7 Receptor Antagonist

Abstract: P2X7 is an extracellular adenosine 5′-triphopshate (ATP)-gated cation channel present on leukocytes, where its activation induces pro-inflammatory cytokine release and ectodomain shedding of cell surface molecules. Human P2X7 can be partially inhibited by amiloride and its derivatives at micromolar concentrations. This study aimed to screen a library of compounds derived from amiloride or its derivative 5-(N,N-hexamethylene) amiloride (HMA) to identify a potential P2X7 antagonist. 6-Furopyridine HMA (6-FPHMA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Half-maximal inhibitory concentration (IC50) values are similar for a large number of selective P2X7 antagonists, as well as the less selective P2X7 antagonists BBG and KN-62 (Bhattacharya, et al, 2013, Chrovian, et al, 2018, Letavic, et al, 2017, Michel, et al, 2009, Roman, et al, 2009. Consistent with earlier studies, which reported the inhibition of human and murine P2X7 by amiloride analogs (Chessell, et al, 1998, Nuttle and Dubyak, 1994, Wiley, et al, 1990, 6-furopyridine hexamethylene amiloride was recently shown to be a nonselective P2X7 antagonist, impairing recombinant English Springer Spaniel and human P2X7 with similar IC50 values (Cuthbertson, et al, 2022). BBG, KN-62, AZ10606120 and AZ11645373 can also impair recombinant English Springer Spaniel P2X7 with similar IC50 values (Spildrejorde, et al, 2014a) to that described elsewhere (Table 1) but other P2X7 antagonists are yet to be tested against the receptor from English Springer Spaniels.…”
Section: Recombinant Canine P2x Receptorssupporting
confidence: 81%
See 1 more Smart Citation
“…Half-maximal inhibitory concentration (IC50) values are similar for a large number of selective P2X7 antagonists, as well as the less selective P2X7 antagonists BBG and KN-62 (Bhattacharya, et al, 2013, Chrovian, et al, 2018, Letavic, et al, 2017, Michel, et al, 2009, Roman, et al, 2009. Consistent with earlier studies, which reported the inhibition of human and murine P2X7 by amiloride analogs (Chessell, et al, 1998, Nuttle and Dubyak, 1994, Wiley, et al, 1990, 6-furopyridine hexamethylene amiloride was recently shown to be a nonselective P2X7 antagonist, impairing recombinant English Springer Spaniel and human P2X7 with similar IC50 values (Cuthbertson, et al, 2022). BBG, KN-62, AZ10606120 and AZ11645373 can also impair recombinant English Springer Spaniel P2X7 with similar IC50 values (Spildrejorde, et al, 2014a) to that described elsewhere (Table 1) but other P2X7 antagonists are yet to be tested against the receptor from English Springer Spaniels.…”
Section: Recombinant Canine P2x Receptorssupporting
confidence: 81%
“…2B), as discussed above, is a key residue within the allosteric drug binding pocket in the extracellular loop. Canine P2X7 containing this SNP is inhibited by numerous P2X7 antagonists (Bartlett, et al, 2017, Cuthbertson, et al, 2022, Spildrejorde, et al, 2014a, but whether this SNP alters antagonist sensitivity remains to be determined. R365Q appears unique to dogs of Labrador Retriever ancestry (Sophocleous, et al, 2020c) but the significance of this finding remains to be investigated.…”
Section: Polymorphic Variants Of Canine P2x Receptorsmentioning
confidence: 99%
“…The P2X7 activity in cells was assessed using an ATP-induced uptake of YO-PRO-1 2+ as described [ 27 ]. Human RPMI 8226 and mouse J774 cells were washed and resuspended in low divalent medium (LDM) (145 mM NaCl, 5 mM KCl, 0.2 mM CaCl 2, 13 mM glucose, and 10 mM HEPES, pH 7.5) (300× g for 5 min) (1 × 10 6 cells/mL).…”
Section: Methodsmentioning
confidence: 99%
“…61,62 Furthermore, we recently published an evaluation of 94 and related analogs for activity at the trimeric ligand-gated ion channel P2X7, a key regulator of peripheral and central inflammation and known off-target of amiloride, finding no significant difference in inhibitory activity when compared to amiloride in whole-cell functional assays. 63 An intensive study by Pamnani and co-workers in the 1980s demonstrated that intravascular administration of 6-iodoamiloride elicited rapid, transient decreases in systemic blood pressure in normotensive dogs with higher potency than amiloride. 64 Further study in wild-type and hypertensive rats determined a hypotensive activity for 6-iodoamiloride not able to be attributed to effects on blood Na + and K + levels or diuresis also observed upon administration.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Relative to amiloride, 6-iodoamiloride 94 shows moderately decreased ENaC activity (the K + -sparing and diuretic target of the parent drug), and modestly improved potency at the sodium–hydrogen exchanger, isoform 1 (NHE1). ,, 6-iodoamiloride has been used as a probe of Na + -mediated processes in diverse settings, including in elucidation of the mechanisms of Na + -driven bacterial flagellar motion . In addition to differing selectivity for the classical Na + -driven targets of amiloride, 94 also shows improved inhibitory activity against the uPA, a TLSP known to play roles in cancer progression and inflammatory disorders. , The enhanced activity of 94 has been attributed to enhanced occupation of the S1β subsite of the uPA proteolytic domain, a tractable amiloride pharmacophore that has been extensively characterized by multiple groups. , Furthermore, we recently published an evaluation of 94 and related analogs for activity at the trimeric ligand-gated ion channel P2X7, a key regulator of peripheral and central inflammation and known off-target of amiloride, finding no significant difference in inhibitory activity when compared to amiloride in whole-cell functional assays …”
Section: Discussionmentioning
confidence: 99%